Early detachment of prosthetic aortic valve one year after replacement for severe aortic regurgitation due to perforated aortic valve aneurysm; a case of suspected HLA-B52 positive Behçet's disease. Issue 3 (September 2020) - Haruki, Nobuhiko; Sumi, Naoki; Kobara, Satoshi; Tsujimoto, Daiki; Iwasaki, Yoichiro; Shimizu, Takashi; Ishii, Hiroshige; Inoue, Yoshiaki; Soeda, Takeshi; Saito, Yuhei; Shirota, Kinya
Abstract: Herein, we report a case of 61-year-old male with congestive heart failure (HF) due to severe aortic regurgitation (AR) caused by ruptured aortic valve aneurysm (VA). Aortic valve replacement (AVR) was performed after improvement of HF symptoms. Pathological examination of resected aortic VA showed neutrophil infiltration. Although he did not have typical clinical features associated with infective endocarditis (IE) such as fever, leukocytosis, or positive blood culture, we misdiagnosed this case as "concealed IE". However, we reconsidered the etiology because prosthetic aortic valve detachment occurred only one year after AVR. When considering causes except IE for perforated aortic VA and early prosthetic valve detachment, Behçet's disease (BD) was more likely based on the clinical course, echocardiography, and pathological findings in this case. The inflammatory process of BD is associated with aortic valvulitis/aortitis, leading to a possible cause of aortic regurgitation due to aortic VA or early prosthetic valve detachment. The diagnosis of BD was challenging in this case because he did not have predominant clinical findings, including recurrent oral ulcer which is a mandatory criterion for the diagnosis by the International Study Group, however, cardiac involvement may have been the initial presentation of BD. <Leaning objective: Aortic valve aneurysm and its rupture are rare and most cases are caused by infective endocarditis (IE). However, if there is no typical clinical feature of IE including fever, leukocytosis, or positive blood culture in such case, Behçet's disease BD should be considered even if there are no predominant clinical findings including recurrent oral ulcer. Appropriate immunosuppressive therapy and modification of surgical techniques for the possible cardiac involvement may improve prognosis in patients with BD.>